DISTINCTIVE FEATURES OF DEVELOPING CRITICAL AND LOGICAL THINKING IN ENGLISH LANGUAGE TEACHING - Aripova Ulbosin Muxametkarim qizi (International Journal of Literature and Language Studies, 2026)
The development of critical and logical thinking has become one of the key objectives of contemporary education, particularly in the context of foreign language teaching. These cognitive skills enable learners to analyze information, evaluate arguments, solve problems, make informed decisions, and actively participate in academic and social communication. This article examines the distinctive pedagogical, psychological, methodological, cultural, and linguistic features of developing critical and logical thinking in English language teaching. The study analyzes theoretical perspectives and research findings of national and international scholars regarding the integration of critical thinking into language education. Special attention is given to learner-centered, interactive, and problem-based teaching approaches that foster higher-order thinking skills.